Understanding Natural Symptoms Through a Scientific Approach in Kindergarten Boys III Bangko, Merangin Regency - Fithri Azni (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research is related to natural phenomena and it is necessary to find an appropriate approach or learning method, one of which is to use a scientific approach. This study aims to "Understanding Natural Symptoms Through A Scientific Approach In The Center Of Natural Materials In TK Putra IIi Bangko Kabupaten Merangin ". This study used a qualitative approach. This descriptive method took the subject of research in group B2 in the center of natural materials at TK Putra III Bangko Kabupaten Merangin Data collection techniques using observation and documentation. Data reduction analysis techniques, data display, verification and draw conclusions. Technique of guaranteeing the validity of the data by triangulation. With the results of learning to improve understanding of natural phenomena through a scientific approach in the natural materials center of TK Putra III Bangko Kabupaten Merangin, learning is carried out to improve understanding of natural phenomena through a scientific approach in the center of natural materials, TK Putra IIi Bangko Kabupaten Merangin, an assessment of group discussions with a scientific approach to natural phenomena so that it can be said that the understanding of natural phenomena using a scientific approach to children in group B2 TK Putra III is good and there is an increase in students' understanding in flood video discussions. The application of this scientific approach has a positive impact in increasing the understanding of natural phenomena from the videos watched, besides the knowledge of B2 grade students in natural phenomena that occur also increases.